Understanding video games the essential introduction - Egenfeldt-Nielsen, Simon 1975-; Smith, Jonas Heide; Tosca, Susana Pajares (Routledge, Taylor & Francis Group, 2024)
The fifth edition of this pioneering textbook takes video game studies into the next decade, highlighting changes in mobile, social, and casual gaming.This book introduces students to both the major theories used to analyze games, such as ludology and narratology, and the commercial and organizational aspects of the game industry. Drawing from historical and contemporary examples, this student-friendly text also explores the aesthetics of games, evaluates the cultural position of video games, and considers the potential effects of both violent and "serious" games. This new edition includes updates to the history, statistics, and developments in the vast game studies landscape throughout. The book has been expanded with additional theory, research, and insights from scholars around the world, making it more inclusive and broadening its global perspective.Extensively illustrated and featuring discussion questions, a glossary of key terms, and a detailed video game history timeline, Understanding Video Games, Fifth Edition is an indispensable resource for anyone interested in examining the ways video games are reshaping entertainment, education, and society